Welcoming bad times: COVID-19 frames on Norway's far right. (20th October 2021) - Mjelde, Hilmar
ABSTRACT: Existing literature tends to analyse the long-term evolution of the far right's world-view rather than how it responds to short-term events. This exploratory study, however, analyses how the far right in Norway framed the unprecedented global crisis of COVID-19. The data encompasses 149 Facebook posts, online op-eds, columns, letters to the editor and YouTube videos about COVID-19 published between 1 January and 31 May 2020 by two radical-right parties, three anti-immigration/anti-Islam groups, one neo-Nazi social movement, one long-time neo-Nazi solo activist and a leading alternative media website in Norway. They represent the full range of established and new, minor and leading, and radical and extreme far-right actors from the last four decades. Based on the material analysed, Mjelde identifies four overarching frames related to the world order, governance, immigration and conspiracies, as well as nine subframes. A main finding is that conspiratorial distrust of the government constitutes a master frame that both the radical and the extreme right combine with other frames that reflect key tenets of their world-view. The findings underscore, first, the rigidity of the far right's world-view; second, contradictory views within the far right about the remedy for the pandemic and the state's role; and, finally, that China is emerging as a bogeyman on the US/Trump-friendly far right.